AN ANALYSIS OF INTERVIEW AS A TECHNIQUE TO ASSESS THE STUDENTS' SPEAKING ABILITY - Lestari, Selviani Vidya (2015)
Selviani Vidya Lestari (1100061). An Analysis of Interview as a Technique to Assess the Students' Speaking Ability. Under the supervision of Prof. H. Fuad Abdul Hamied, M.A., Ph.D. and Muhammad Handi Gunawan, M.Pd.The research analyses the implementation and implication of interview as a technique to assess the students' speaking ability. Mix methods research design was used to obtain the data. The data were gathered from 10 eleventh grade students and taken from observation and tests. The tests administered in this research were TOEIC speaking test and interview test. The qualitative data were taken from observation. The observation was conducted during the interview test to see the implementatation of interview. The quantitative data were taken from the students' TOEIC speaking test score and interview test score. The speaking assessment criteria used to score the students' speaking ability through interview was the combination of IELTS and Adam and Frith speaking assessment criteria. The students' TOEIC speaking test score and the interview score were computed by using Pearson Product Moment Correlation formula to see the implication of interview. The findings showed that the implementation of interview was appropriate based on some steps by Underhill (1987). Besides, the interview had covered the components defined by Harris (1969) in the form of the IELTS-Adam and Frith speaking assessment criteria. In addition, the correlation coefficient between the students' TOEIC speaking test score and interview test score was 0,7. It indicated thatthe correlation was strong and positive.This study brought to a close that interview is a good and appropriate technique to assess the students' speaking ability. However, some consideration should be made in the relation of time, setting, and the topic of the interview. Keywords: Interview, Speaking Assessment, TOEIC Speaking Test